Efficacy of Ketamine in the Treatment of Substance Use Disorders: A Systematic Review - Jones, Jennifer L.; Mateus, Camilo F.; Malcolm, Robert J.; Brady, Kathleen T.; Back, Sudie E. (Frontiers in Psychiatry, 2018)
Background: Despite advances in behavioral and pharmacotherapy interventions, substance use disorders (SUDs) are frequently refractory to treatment. Glutamatergic dysregulation has received increasing attention as one common neuropathology across multiple substances of abuse. Ketamine is a potent N-methyl-D-aspartate (NMDA) glutamatergic receptor antagonist which has been found to be effective in the treatment of severe depression. Here we review the literature on the efficacy of ketamine in the treatment of SUDs. Methods: A systematic review of the PubMed, Scopus, and ClinicalTrials.gov databases was undertaken to identify completed and ongoing human studies of the effectiveness of ketamine in the treatment of SUDs between January 1997 and January 2018. Results and conclusion: Seven completed studies were identified. Two studies focused on alcohol use disorder, two focused on cocaine use disorder, and three focused on opioid use disorder. Both cocaine studies found improvements in craving, motivation, and decreased cocaine use rates, although studies were limited by small sample sizes, a homogeneous population and short follow-up. Studies of alcohol and opioid use disorders found improvement in abstinence rates in the ketamine group, with significant between-group effects noted for up to two years following a single infusion, although these were not placebo-controlled trials. These results suggest that ketamine may facilitate abstinence across multiple substances of abuse and warrants broader investigation in addiction treatment. We conclude with an overview of the six ongoing studies of ketamine in the treatment of alcohol, cocaine, cannabis, and opioid use disorders and discuss future directions in this emerging area of research.